Development and measurement validity of an instrument for the impact of technology-mediated learning on learning processes. (June 2018) - Wang, Sufen; Zhang, Kejing; Du, Ming; Wang, Zhijun
Abstract: Technology-mediated learning (TML) has turned out to be essential in classroom in higher education. How to evaluate the effect of TML has become a critical issue in research and practice. Yet, there exists very little understanding of how to measure the effect of TML on learning process. The existing research results are difficult to be used in teaching design. This paper develops an instrument as a diagnostic tool to comprehensively evaluate the effect of TML on learning process. This instrument focuses on the relationship among IT, cognitive information processing, and instructional process. Based on cognitive information processing theory and Gagné's instructional theory, definition and measurement of 8 constructs are identified and designed. In a sample of 181 undergraduates in nine majors, the study finds that this instrument has higher reliability, better convergent validity and discriminant validity. This instrument can help provide rich information about whether and how TML affects instructional events and learning activities effectively. At the same time, it can be a guiding tool for more effective applications of TML in instructional event design. Highlights: Developing a multi-scale instrument to for the effect of TML on learning process. Identifying theoretical constructs and operational definitions for the instrument. Offering an empirical study to verify the validity of the multi-scale instrument.